MOF-derived NiS / ZnIn2S4 composite material as well as preparation method and application thereof
Through MOF derivatization of NiS/ZnIn2S4 composite materials, a heterogeneous interface is constructed and non-precious metal cocatalysts are introduced, which solves the problem of poor photocatalytic performance of ZnIn2S4, and achieves efficient photocatalytic hydrogen evolution effect and material stability improvement.
Patent Information
- Application Number
- CN202411346011.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-07
AI Technical Summary
In the prior art, the photogenerated carrier recombination rate and slow migration rate when used alone in ZnIn2S4, resulting in poor photocatalytic hydrogen evolution performance and difficult to ensure effective interface contact between materials and good electrons at low cost. Coupling to reduce interface defects.
Using MOF-derived NiS/ZnIn2S4 composite material, NiS with microsphere structure is prepared by Ni-MOF as a precursor, combined with helical ZnIn2S4, a heterogeneous interface is constructed, and non-precious metal cocatalysts are introduced to reduce the activation energy of hydrogen evolution reaction and improve electron transport pathways. .
The photocatalytic hydrogen evolution efficiency is improved, the photocatalytic performance of the material is enhanced, the photocorrosion phenomenon is reduced, and the photocatalytic hydrogen evolution rate of the composite material is improved by optimizing the interface quality.
Smart Images

Figure CN119259081A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, and in particular to a MOF-derived NiS / ZnIn2S4 composite material and a preparation method and application thereof. Background Art
[0002] Due to the growing fossil fuel consumption and the ensuing energy crisis and climate change, it is crucial to find alternatives to renewable energy. Hydrogen (H2) is an environmentally friendly and clean energy source. In the past few decades, a variety of methods for preparing H2 have been developed. With abundant sunlight, photocatalytic hydrogen evolution using semiconductor materials is a promising strategy. However, traditional semiconductor photocatalysts, such as TiO2 and ZnO, have low light utilization efficiency due to their wide band gaps. The two-dimensional binary metal sulfide semiconductor ZnIn2S4 has a suitable band gap of ~2.4eV and can be used to catalyze various photoredox reactions. However, the photocatalytic activity of pure ZnIn2S4 is still relatively poor, mainly due to the high recombination rate and slow migration rate of photogenerated carriers. Loading co-catalysts on semiconductor photocatalysts is an effective way to improve the performance of photocatalysts, because it can not only accelerate the separation of photogenerated electrons and holes, but also reduce the activation energy of proton reduction reactions. Precious metal co-catalysts such as platinum are the most effective for promoting hydrogen production, but their practical application is limited by scarcity and high prices. Metal oxide co-catalysts face the disadvantage of low conductivity.
[0003] In order to solve the problem of high recombination rate and slow migration rate of photogenerated carriers when ZnIn2S4 is used alone, heterostructures are usually constructed, co-catalysts are introduced, and elements are doped to improve the photocatalytic hydrogen evolution performance of ZnIn2S4. However, in the process of constructing heterostructures of ZnIn2S4 and other semiconductor materials, the performance of the heterostructure depends largely on the quality of the structural interface (i.e., the electronic structure and chemical stability at the structural interface and whether an ideal heterojunction interface is formed).
[0004] Therefore, the biggest problem in the prior art is how to ensure effective interface contact and good electronic coupling between the two composite materials at low cost (that is, to have a better structure, while maintaining their respective unique properties, achieving effective electronic coupling and reducing defects at the interface) to improve the photocatalytic hydrogen evolution performance of the material. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a MOF-derived NiS / ZnIn2S4 composite material and a preparation method and application thereof.
[0006] In the first aspect, the present invention provides a MOF-derived NiS / ZnIn2S4 composite material, including: the MOF-derived NiS / ZnIn2S4 composite material is a rope-grape-like material with a coupled heterogeneous interface formed by the composite of spiral ZnIn2S4 and NiS, wherein the NiS is prepared by using Ni-MOF as a precursor, sulfiding and calcining; the spiral ZnIn2S4 is obtained by hydrothermal synthesis using polyvinyl pyrrolidone as a directing agent and serine as a template.
[0007] Description: In the above method, the introduction of MOF-derived non-precious metal co-catalysts into ZnIn2S4 to construct a heterojunction can effectively reduce the photocorrosion phenomenon of ZnIn2S4. The NiS / ZnIn2S4 composite material obtained by using the microsphere structured Ni-MOF as a precursor has more abundant active sites and enhances the photocatalytic efficiency. At the same time, NiS obtained by using Ni-MOF as a precursor as a co-catalyst effectively reduces the activation energy of the hydrogen evolution reaction, and the heterogeneous interface constructed between it and ZnIn2S4 changes the electron transmission pathway and inhibits the recombination of electron-hole pairs. Therefore, the above metal organic framework-derived NiS / ZnIn2S4 composite material has excellent performance advantages in the field of photocatalytic hydrogen evolution.
[0008] In a second aspect, the present invention further provides a method for preparing a MOF-derived NiS / ZnIn2S4 composite material, comprising:
[0009] Take deionized water, HCl aqueous solution and glycerol and mix them evenly, add NiS and dissolve it by ultrasonication; then add spiral ZnIn2S4, stir and dissolve it, place it in a container, heat it in an oil bath at 70-90℃ for 4-8h; then cool it;
[0010] After cooling to room temperature, centrifugation and washing with ethanol solution are performed, and then drying is performed at 50-70°C for 10-14h to obtain NiS / ZnIn2S4;
[0011] The addition ratio of the deionized water, HCl aqueous solution, propylene glycol, NiS, and spiral ZnIn2S4 is: 30-40 mL: 3-8 mL: 2 mL: 3-20 mg: 140-160 mg, wherein the pH of the HCl aqueous solution is 2.5.
[0012] The preparation method of NiS comprises:
[0013] S1-1, preparation of Ni-MOF: stirring and dissolving nickel nitrate into an aqueous solution containing methanol, adding sodium citrate and disodium ethylenediaminetetraacetate in sequence, dissolving sodium citrate and disodium ethylenediaminetetraacetate to form a mixed solution, reacting the mixed solution at 160-210°C for 20-28h, cooling to room temperature, centrifuging and washing with deionized water and ethanol solution, and then drying at 50-70°C for 10-14h to obtain a Ni-MOF precursor;
[0014] S1-2, preparation of NiS hollow spheres: ultrasonically dissolve the Ni-MOF precursor obtained in S1-1 into ethanol, add thioacetamide; after stirring and dissolving, react at 160-210° C. for 4-10 hours; then cool to room temperature, centrifuge and wash with ethanol, and then dry at 50-70° C. for 10-14 hours to obtain NiS particles, and calcine the NiS particles in a nitrogen atmosphere to obtain NiS.
[0015] Description: Through the above preparation method, the high specific surface area, rich porous structure and metal sites of metal organic framework materials (MOF) can be fully utilized to prepare Ni-MOF with a microsphere structure, which can enhance the bonding effect of the two in NiS / ZnIn2S4 composite materials and improve the interface quality of the composite structure, thereby increasing the hydrogen evolution rate of the composite material.
[0016] Furthermore, the preparation method of the spiral ZnIn2S4 comprises:
[0017] 1) Dissolve 0.4-0.7 mmol of zinc nitrate and 0.9-1.2 mmol of indium nitrate in 15-30 mL of deionized water to form a first mixed solution;
[0018] 2) Add 0.05-0.3 g of polyvinyl pyrrolidone and 0.02-0.07 g of serine to the first mixed solution, stir until dissolved, add 0.02-0.07 mmol / mL of CH3CSNH2 aqueous solution and stir; then stand at 150-200°C for 20-25 hours, and obtain spiral ZnIn2S4 after centrifugal separation, washing and drying.
[0019] Furthermore, the spiral ZnIn2S4 is subjected to surface modification treatment;
[0020] 3) Surface modification methods include:
[0021] Take an aqueous solution of hexadecyltrimethylammonium bromide with a mass fraction of 20%, add the spiral ZnIn2S4 to the aqueous solution of hexadecyltrimethylammonium bromide at a ratio of 1g:10ml, and mix the two thoroughly by magnetic stirring or ultrasonic treatment; heat and stand at 40-50°C for 2-3h, and then take out the pretreated ZnIn2S4;
[0022] Using 0.1M sodium sulfate solution as the electrolyte, the pretreated ZnIn2S4 was fixed on the conductive glass as the working electrode, a platinum sheet was used as the counter electrode, and an Ag / AgCl electrode was used as the reference electrode. At a voltage of 0.5V and a current density of 0.8-1.2mA / cm 2 After constant potential electrolysis for 10 min, the surface of the ZnIn2S4 was washed with deionized water and ethanol and dried.
[0023] Description: Through the above method, ZnIn2S4 can have higher photocatalytic performance, better stability, and higher selectivity. More active sites can be introduced on the surface of ZnIn2S4 to improve its absorption and conversion efficiency of light energy. The stability of the ZnIn2S4 structure can be enhanced to avoid the destruction of the spiral shape during the photocatalytic process. The treated ZnIn2S4 surface improves its hydrophilicity, which is beneficial to the photocatalytic reaction.
[0024] Furthermore, in the S1-1, the addition ratio of nickel nitrate, methanol aqueous solution, sodium citrate, and disodium ethylenediaminetetraacetate is 1-3 g: 30 ml: 1-2 g: 1-3 g; wherein the methanol aqueous solution is obtained by mixing methanol and deionized water in a volume ratio of 1:3;
[0025] In the S1-2, the addition ratio of Ni-MOF precursor, ethanol and thioacetamide is: 20-40 mg: 40 ml: 100 mg.
[0026] Note: The composite material prepared by using the above-mentioned component ratio has a better structural morphology, and better catalytic performance, stability and other properties.
[0027] Furthermore, when the NiS particles are calcined in a nitrogen atmosphere, the calcination temperature is 250-350° C. and the calcination time is 20-40 min.
[0028] Note: The above calcination conditions can form hollow spherical NiS. The hollow structure can further shorten the carrier transmission path and improve the photocatalytic hydrogen evolution effect.
[0029] Furthermore, the method of calcining NiS particles in a nitrogen atmosphere is: first, the NiS particles are heated from 20-25°C to 250-350°C at a heating rate of 3-8°C / min, then kept at 250-350°C for 20-40min, and then cooled to 20-25°C at a cooling rate of 5-10°C / min.
[0030] Note: The above calcination method can form a relatively uniform hollow spherical (i.e. hollow spherical) NiS. The hollow spherical structure has a better combination effect with ZnIn2S4, and the quality of the obtained composite material is higher, that is, the photocatalytic hydrogen evolution performance is better.
[0031] Furthermore, the power of the ultrasound is 300-500W, and the time is 20-35min. In the centrifugal washing, the centrifugal speed is 5000-8000r / min, and the centrifugal time is 4-10min.
[0032] Furthermore, it is applied in the process of photocatalytic hydrogen evolution.
[0033] The beneficial effects of the present invention are:
[0034] The present invention introduces a MOF-derived non-precious metal co-catalyst into ZnIn2S4 to construct a heterojunction, which can effectively reduce the photocorrosion phenomenon of ZnIn2S4. The NiS / ZnIn2S4 composite material obtained by using a microsphere structured Ni-MOF as a precursor has more abundant active sites and enhances the photocatalytic efficiency. At the same time, through the setting of the preparation method, the obtained hollow spherical NiS is used as a co-catalyst to effectively reduce the activation energy of the hydrogen evolution reaction, and the heterogeneous interface constructed between the NiS and ZnIn2S4 changes the transmission pathway of electrons and inhibits the recombination of electron-hole pairs. Therefore, the above-mentioned metal organic framework-derived NiS / ZnIn2S4 composite material has excellent performance advantages in the field of photocatalytic hydrogen evolution. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a graph showing the XRD test results of the NiS / ZnIn2S4 composite material prepared in Example 1 of the present invention;
[0036] Figure 2 This is a standard comparison diagram of the SEM test results of the NiS / ZnIn2S4 composite material prepared in Example 1 of the present invention;
[0037] Figure 3 1 is a TEM test result diagram of the NiS / ZnIn2S4 composite material prepared in Example 1 of the present invention;
[0038] Figure 4 This is a graph showing the XPS test results of the NiS / ZnIn2S4 composite material prepared in Example 1 of the present invention;
[0039] Figure 5 This is a UV-visible diffuse reflectance spectrum test result diagram of the NiS / ZnIn2S4 composite material prepared in Example 1 of the present invention
[0040] Figure 6This is a graph showing the transient photocurrent test results of the NiS / ZnIn2S4 composite material prepared in Example 1 of the present invention;
[0041] Figure 7 1 is a graph showing the electrochemical impedance test results of the NiS / ZnIn2S4 composite material prepared in Example 1 of the present invention;
[0042] Figure 8 is a Mott-Schottky curve diagram of the NiS / ZnIn2S4 composite material prepared in Example 1 of the present invention;
[0043] Fig. 9 This is a test diagram of the photocatalytic hydrogen evolution activity of the NiS / ZnIn2S4 composite material prepared in Example 1 of the present invention;
[0044] Fig.10 This is a diagram of the photocatalytic reaction mechanism of the NiS / ZnIn2S4 composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0045] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.
[0046] Embodiment 1:
[0047] S1. S1-1. Preparation of Ni-MOF:
[0048] Stir and dissolve 2.326g of nickel nitrate in a mixed solution containing 20mL of deionized water and 10mL of methanol. Then add 1.2g of sodium citrate and 1.49g of disodium ethylenediaminetetraacetate in sequence. After the solution is completely stirred and dissolved, transfer the mixed solution to a reactor and react at 200°C for 24h. After the reaction is completed, cool to room temperature, centrifuge and wash with deionized water and ethanol solution, and finally place the sample in a drying oven at 60°C for 12h to obtain a Ni-MOF precursor;
[0049] S1-2, preparation of NiS:
[0050] Ultrasonic dissolve 30 mg Ni-MOF in 40 mL ethanol solution, add 100 mg thioacetamide. After fully stirring and dissolving, transfer the mixed solution into a reactor and react at 200 ° C for 6 hours. After the reaction is completed, cool to room temperature, centrifuge and wash with ethanol solution, and finally place the sample in a drying oven at 60 ° C for 12 hours; place the prepared NiS in a tubular furnace, calcine in a nitrogen atmosphere, and keep the reaction at 300 ° C for 30 minutes;
[0051] S2. Preparation of spiral ZnIn2S4:
[0052] 1) Dissolve 0.5 mmol of zinc nitrate and 1 mmol of indium nitrate in 20 mL of deionized water to form a first mixed solution;
[0053] 2) Add 0.1 g of polyvinyl pyrrolidone and 0.05 g of serine to the first mixed solution, stir until dissolved, add 0.05 mmol / mL of CH3CSNH2 aqueous solution, and stir; then stand at 180°C for 24 hours, and obtain spiral ZnIn2S4 after centrifugal separation, washing, and drying;
[0054] S3. Preparation of NiS / ZnIn2S4:
[0055] Mix 34 mL of deionized water, 4 mL of HCl aqueous solution and 2 mL of propylene glycol, add 5 mg of NiS and dissolve it by ultrasound; add 150 mg of spiral ZnIn2S4, stir and dissolve it, then place it in a flask and place it in an oil bath at 80°C for 6 hours; after the reaction is completed and wait for it to cool to room temperature, wash it by centrifugation with ethanol solution, and finally place the sample in a drying oven at 60°C for 12 hours to obtain NiS / ZnIn2S4.
[0056] Example 2
[0057] The difference between this embodiment and embodiment 1 is that the amount of NiS added in step S3 is different, and 10 mg NiS is added and dissolved by ultrasound.
[0058] Example 3
[0059] The difference between this embodiment and embodiment 1 is that the amount of NiS added in step S3 is different, and 15 mg NiS is added and dissolved by ultrasound.
[0060] Example 4
[0061] The difference between this embodiment and embodiment 1 is that the components of the raw materials in steps S1-1 and S1-2 are different, and the added amounts of nickel nitrate, methanol aqueous solution, sodium citrate, and disodium ethylenediaminetetraacetate are 1g:30ml:2g:1g respectively.
[0062] Example 5
[0063] The difference between this embodiment and embodiment 1 is that the components of the raw materials in steps S1-1 and S1-2 are different, and the added amounts of nickel nitrate, methanol aqueous solution, sodium citrate, and disodium ethylenediaminetetraacetate are 3g:30ml:1g:3g respectively.
[0064] Example 6
[0065] The difference between this embodiment and embodiment 1 is that the components of the raw materials in step S3 are different, and the added amounts of deionized water, HCl aqueous solution, propylene glycol, NiS, and spiral ZnIn2S4 are 30 mL: 3 mL: 2 mL: 3 mg: 160 mg, respectively.
[0066] Example 7
[0067] The difference between this embodiment and embodiment 1 is that the components of the raw materials in step S3 are different, and the added amounts of deionized water, HCl aqueous solution, propylene glycol, NiS, and spiral ZnIn2S4 are 40 mL: 8 mL: 2 mL: 20 mg: 140 mg, respectively.
[0068] Example 8
[0069] The difference between this embodiment and embodiment 1 is that the reaction parameters in the above preparation method are different.
[0070] S1-1. Preparation of Ni-MOF: stirring and dissolving nickel nitrate into an aqueous solution containing methanol, adding sodium citrate and disodium ethylenediaminetetraacetate in sequence, and forming a mixed solution after sodium citrate and disodium ethylenediaminetetraacetate are dissolved, reacting the mixed solution at 210°C for 20h, cooling to room temperature, centrifuging and washing with deionized water and ethanol solution, and then drying at 50°C for 10h to obtain a Ni-MOF precursor;
[0071] S1-2, preparation of NiS hollow spheres: ultrasonically dissolve the Ni-MOF precursor obtained in S1-1 in ethanol, add thioacetamide; after stirring and dissolving, react at 210°C for 10 hours; then cool to room temperature, centrifuge and wash with ethanol, and then dry at 70°C for 10 hours to obtain NiS particles, and calcine the NiS particles in a nitrogen atmosphere to obtain NiS.
[0072] S2. Preparation of spiral ZnIn2S4:
[0073] 1) Dissolve 0.4 mmol of zinc nitrate and 0.9 mmol of indium nitrate in 15 mL of deionized water to form a first mixed solution;
[0074] 2) Add 0.05 g of polyvinyl pyrrolidone and 0.02 g of serine to the first mixed solution, stir until dissolved, add 0.02 mmol / mL of CH3CSNH2 aqueous solution, and stir; then stand at 150°C for 20 h, and obtain spiral ZnIn2S4 after centrifugal separation, washing, and drying;
[0075] S3. Preparation of NiS / ZnIn2S4:
[0076] Take deionized water, HCl aqueous solution and glycerol and mix them evenly, add NiS and dissolve it by ultrasonication; then add spiral ZnIn2S4, stir and dissolve it, place it in a container, heat it in an oil bath at 90℃ for 8h; then cool it;
[0077] After cooling to room temperature, the mixture was washed by centrifugation with ethanol solution and then dried at 50°C for 10 h to obtain NiS / ZnIn2S4.
[0078] Example 9
[0079] The difference between this embodiment and embodiment 1 is that the reaction parameters in the above preparation method are different.
[0080] S1-1. Preparation of Ni-MOF: stirring and dissolving nickel nitrate into an aqueous solution containing methanol, adding sodium citrate and disodium ethylenediaminetetraacetate in sequence, and dissolving sodium citrate and disodium ethylenediaminetetraacetate to form a mixed solution, reacting the mixed solution at 190°C for 28h, cooling to room temperature, centrifuging and washing with deionized water and ethanol solution, and then drying at 70°C for 14h to obtain a Ni-MOF precursor;
[0081] S1-2, preparation of NiS hollow spheres: ultrasonically dissolve the Ni-MOF precursor obtained in S1-1 in ethanol, add thioacetamide; after stirring and dissolving, react at 190°C for 4 hours; then cool to room temperature, centrifuge and wash with ethanol, and then dry at 50°C for 14 hours to obtain NiS particles, and calcine the NiS particles in a nitrogen atmosphere to obtain NiS.
[0082] S2. Preparation of spiral ZnIn2S4:
[0083] 1) Dissolve 0.7 mmol of zinc nitrate and 1.2 mmol of indium nitrate in 30 mL of deionized water to form a first mixed solution;
[0084] 2) Add 0.3 g of polyvinyl pyrrolidone and 0.07 g of serine to the first mixed solution, stir until dissolved, add 0.07 mmol / mL of CH3CSNH2 aqueous solution, and stir; then stand at 200°C for 25 h, and obtain spiral ZnIn2S4 after centrifugal separation, washing, and drying;
[0085] S3. Preparation of NiS / ZnIn2S4:
[0086] Take deionized water, HCl aqueous solution and glycerol and mix them evenly, add NiS and dissolve it by ultrasonication; then add spiral ZnIn2S4, stir and dissolve it, place it in a container, heat it in an oil bath at 70℃ for 4h; then cool it;
[0087] After cooling to room temperature, the mixture was washed by centrifugation with ethanol solution and then dried at 70°C for 14 h to obtain NiS / ZnIn2S4.
[0088] Example 10
[0089] The present embodiment is different from the embodiment 1 in that the calcination method is different, specifically, the temperature is raised from room temperature to 300°C at a heating rate of 5°C / min, the temperature is kept at 300°C for 30 minutes, and finally the temperature is lowered from 300°C to room temperature to obtain NiS.
[0090] Embodiment 11
[0091] The difference between this embodiment and embodiment 1 is that the spiral ZnIn2S4 is surface modified, and the surface modification method includes:
[0092] Take a 20% aqueous solution of hexadecyltrimethylammonium bromide by mass fraction, add the spiral ZnIn2S4 to the aqueous solution of hexadecyltrimethylammonium bromide at a ratio of 1g:10ml, and mix the two thoroughly by magnetic stirring or ultrasonic treatment; heat and stand at 45°C for 2.5h, and then take out the pretreated ZnIn2S4;
[0093] Using 0.1M sodium sulfate solution as the electrolyte, the pretreated ZnIn2S4 was fixed on the conductive glass as the working electrode, a platinum sheet was used as the counter electrode, and an Ag / AgCl electrode was used as the reference electrode. At a voltage of 0.5V and a current density of 1mA / cm 2 After constant potential electrolysis for 10 min, the surface of the ZnIn2S4 was washed with deionized water and ethanol and dried.
[0094] Example 12
[0095] The difference between this embodiment and embodiment 1 is that the spiral ZnIn2S4 is surface modified, and the surface modification method includes:
[0096] Take a 20% aqueous solution of hexadecyltrimethylammonium bromide by mass, add the spiral ZnIn2S4 to the aqueous solution of hexadecyltrimethylammonium bromide at a ratio of 1g:10ml, and mix the two thoroughly by magnetic stirring or ultrasonic treatment; heat and stand at 40°C for 3h, and then take out the pretreated ZnIn2S4;
[0097] Using 0.1 M sodium sulfate solution as the electrolyte, the pretreated ZnIn2S4 was fixed on the conductive glass as the working electrode, a platinum sheet was used as the counter electrode, and an Ag / AgCl electrode was used as the reference electrode. At a voltage of 0.5 V and a current density of 1.2 mA / cm 2After constant potential electrolysis for 10 min, the surface of the ZnIn2S4 was washed with deionized water and ethanol and dried.
[0098] Example 13
[0099] The difference between this embodiment and embodiment 1 is that the spiral ZnIn2S4 is surface modified, and the surface modification method includes:
[0100] Take an aqueous solution of hexadecyltrimethylammonium bromide with a mass fraction of 20%, add the spiral ZnIn2S4 to the aqueous solution of hexadecyltrimethylammonium bromide at a ratio of 1g:10ml, and mix the two thoroughly by magnetic stirring or ultrasonic treatment; heat and stand at 50°C for 2h, and then take out the pretreated ZnIn2S4;
[0101] Using 0.1M sodium sulfate solution as the electrolyte, the pretreated ZnIn2S4 was fixed on the conductive glass as the working electrode, a platinum sheet was used as the counter electrode, and an Ag / AgCl electrode was used as the reference electrode. At a voltage of 0.5V and a current density of 0.8mA / cm 2 After constant potential electrolysis for 10 min, the surface of the ZnIn2S4 was washed with deionized water and ethanol and dried.
[0102] Comparative Example 1: The flaky BPQDs / ZnIn2S4 binary heterostructure photocatalytic material disclosed in the patent application with application number CN202210924878.9;
[0103] Comparative Example 2: Using NiS2 in the prior art instead of NiS to perform the operation of step S3, that is, compounding with ZnIn2S4 to obtain a NiS2 / ZnIn2S4 composite material;
[0104] Comparative Example 3: Using the nano-sheet ZnIn2S4 in the prior art to obtain a NiS / ZnIn2S4 composite material;
[0105] Comparative Example 4: Ni-MOF was not used as a precursor, and NiS was prepared by a template method using polymer microspheres as templates.
[0106] Experimental example:
[0107] 1. Morphological characterization: Figure 1 As shown,
[0108] Experimental Example 1
[0109] Taking the process parameters of the method in Example 1 of the present invention as an example, the NiS / ZnIn2S4 composite material of the present invention is subjected to XRD test. Figure 1As shown in the figure, the diffraction peaks of the NiS / ZnIn2S4 composite material at 21.6, 27.7, and 47.2 correspond to the (006), (102), and (110) crystal planes in the PDF standard card (JCPDS.65-2023) of ZnIn2S4. The diffraction peaks of the NiS / ZnIn2S4 composite material at 31.59, 38.78, 53.65, and 35.31 correspond to the (200), (211), (311), and (210) crystal planes in the NiS PDF standard card (JCPDS.11-0099).
[0110] Experimental Example 2
[0111] Taking the process parameters of the method in Example 1 of the present invention as an example, the NiS / ZnIn2S4 composite material of the present invention was subjected to SEM testing. Figure 2 Shown is the structure of ZnIn2S4.
[0112] Experimental Example 3
[0113] Taking the process parameters of the method in Example 1 of the present invention as an example, the NiS / ZnIn2S4 composite material of the present invention was subjected to TEM test. Figure 3 shown.
[0114] Experimental Example 4
[0115] Taking the process parameters of the method in Example 1 of the present invention as an example, XPS test was performed on the NiS / ZnIn2S4 composite material of the present invention. Figure 4 The Ni 2p spectrum in (a) clearly shows two peaks of Ni 2p3 / 2 at 854.0eV and 857.9eV and two peaks of Ni 2p1 / 2 at 871.5eV and 877eV, which belong to the main peak and satellite peak of Ni 2p3 / 2 and Ni 2p1 / 2 in NiS / ZnIn2S4, respectively. The peaks at 161.7eV and 162.9eV correspond to S2p3 / 2 and S2p1 / 2, respectively. Figure 4 (b)). Figure 4 The characteristic binding energies of In3d5 / 2 and In 3d3 / 2 in (c) are 445.0 eV and 452.6 eV, respectively, indicating the formation of In3+. Figure 4-4 The characteristic binding energies of Zn2p3 / 2 and Zn2p1 / 2 in (d) are 1022.6 eV and 1045.7 eV, respectively, indicating the formation of Zn2+.
[0116] Experimental Example 5
[0117] Taking the process parameters of the method in Example 1 of the present invention as an example, the NiS / ZnIn2S4 composite material of the present invention was tested by UV-visible diffuse reflectance spectroscopy. Figure 5As shown in (a), pure ZnIn2S4 has an absorption edge at 599nm, but no absorption in the wavelength range of 600-800nm. Although loading NiS on ZnIn2S4 does not significantly change its original strong light response range, the introduction of NiS makes the NiS / ZnIn2S4 nanocomposite material exhibit enhanced absorption performance in the visible light region of 500-800nm. The strong light response ability of NiS may be due to the strong absorption intensity of black powder under UV-visible light. In addition, the red shift of the light absorption range of NiS / ZnIn2S4 composite material is mainly controlled by the high refractive index loaded NiS, which means the effective utilization of sunlight and higher charge separation of NiS / ZnIn2S4 composite material. According to Figure 4-5 (a) Draw Tauc Figure 5 (b) According to the different types of semiconductors, n is taken as 1 / 2 when calculating ZnIn2S4. NiS is a co-catalyst and has no band structure, so it is not calculated. The calculated band gap value of ZnIn2S4 is 2.09eV.
[0118] Experimental Example 6
[0119] Taking the process parameters of the method in Example 1 of the present invention as an example, a transient photocurrent test was performed on the NiS / ZnIn2S4 composite material of the present invention. Figure 6 As shown in Figure 2, NiS generates essentially no photocurrent signal under illumination. Compared with pure NiS and pure ZnIn2S4, the NiS / ZnIn2S4 composite generates a more stable and higher photocurrent, indicating that the loading of NiS is beneficial for denser light collection, promoting more efficient electron-hole separation and faster charge transfer.
[0120] Experimental Example 7
[0121] Taking the process parameters of the method in Example 1 of the present invention as an example, an electrochemical impedance test was performed on the NiS / ZnIn2S4 composite material of the present invention. Figure 7 As shown in the figure, the NiS / ZnIn2S4 composite material exhibits a smaller arc radius, which means that its charge transfer resistance is relatively small. Therefore, the mobility of photogenerated electrons in it is improved, and the separation effect of electron-hole pairs is more significant.
[0122] Experimental Example 8
[0123] Taking the process parameters of the method in Example 1 of the present invention as an example, the Mott-Schottky curve test was performed on the NiS / ZnIn2S4 composite material of the present invention. Figure 8As shown in the figure, the slopes of the curves of NiS and ZnIn2S4 are both positive, which clearly shows that NiS and ZnIn2S4 are both n-type semiconductors. According to the formula, the flat band potential of NiS and ZnIn2S4 is calculated to be -0.21eV and -0.36eV, respectively, and the valence band potentials correspond to -0.41eV and -0.56eV vs NHE.
[0124] 2. Effect comparison
[0125] Experimental Example 9
[0126] Taking the process parameters of the method in Example 1 of the present invention as an example, the photocatalytic hydrogen evolution activity of the NiS / ZnIn2S4 composite material of the present invention was tested. Fig. 9 (a) It can be seen that NiS itself has no hydrogen evolution activity, but after the hollow microsphere NiS is loaded on the ZnIn2S4 two-dimensional nanosheet to form a heterogeneous interface, the hydrogen evolution rate is significantly improved. This shows that NiS itself does not have the ability to generate hydrogen as an active photocatalyst, but plays the role of a co-catalyst. In this process, the light-induced recombination phenomenon of photogenerated electron-hole pairs is effectively suppressed, and the transfer of photogenerated electrons within the heterogeneous interface is significantly promoted. With the increase in the amount of co-catalyst NiS added, the photocatalytic hydrogen evolution rate of the NiS / ZnIn2S4 composite material shows a gradual decreasing trend. This may be because when NiS is added in excess, it covers the surface of ZnIn2S4, forming a carrier recombination center or blocking the active site, thereby inhibiting the light penetration inside the material, producing a "light-shielding effect" and affecting the photocatalytic hydrogen evolution rate. Therefore, in order to achieve the optimal photocatalytic activity of the ZnIn2S4 photocatalyst, it is particularly critical to control the loading amount of NiS to an appropriate level. By Fig. 9 (b) It can be seen that when 5 mg NiS is added, the hydrogen evolution rate of the NiS / ZnIn2S4 composite material is relatively high, which is 12244.96 μmol g-1h-1, which is nearly 14.5 times that of the single ZnIn2S4. In the NiS / ZnIn2S4 composite material, NiS is used as a co-catalyst. The addition of the co-catalyst changes the transmission pathway of the photogenerated charge and also provides more active sites, further effectively improving the hydrogen evolution activity. The optimal hydrogen evolution rate of the BPQDs / ZnIn2S4 composite material in Comparative Example 1 is 1407 μmol g -1 h -1The hydrogen evolution rate of NiS / ZnIn2S4 prepared in Example 1 of the present invention is nearly 9 times that of Comparative Example 1; Comparative Example 2, Comparative Example 3 and Comparative Example 4 are approximately 0.5-0.6 times, 0.65 times and 0.7 times the hydrogen evolution rate of Example 1 of the present invention, respectively; it can be seen that the effect of Example 1 of the present invention is better; in addition, by comparing Example 1 with Example 11, it is found that the hydrogen evolution rate of Example 11 is about 1.5 times that of Example 1, indicating that the method of Example 11 can improve the effect of photocatalytic hydrogen evolution.
[0127] Experimental Example 10
[0128] Taking the process parameters of the method in Example 1 of the present invention as an example, the photocatalytic hydrogen evolution activity of the NiS / ZnIn2S4 composite material of the present invention was tested. Fig.10 As shown in the figure, under light, both NiS and ZnIn2S4 are excited to generate electron-hole pairs. Due to the potential difference between the valence band and the conduction band of the two, the electrons in the conduction band of ZnIn2S4 can easily migrate to the conduction band of NiS through the heterogeneous interface. At the same time, the photogenerated holes on the surface of ZnIn2S4 can react with TEOA to generate pyruvic acid. In summary, NiS / ZnIn2S4 effectively achieves the separation of photogenerated electron-hole pairs under light, significantly improving the generation of hydrogen. By combining NiS with ZnIn2S4, we successfully constructed unique charge transfer nanochannels in the heterogeneous interface. These nanochannels benefit from the excellent properties of the heterogeneous interface and achieve efficient charge transfer. At the same time, this composite structure significantly reduces the time of charge transfer, and ultimately makes NiS / ZnIn2S4 have efficient photocatalytic hydrogen evolution activity. At the same time, NiS can act as a co-catalyst and electron scavenger to promote the separation of photogenerated carriers, thereby further improving the hydrogen production rate of the composite material.
Claims
1. A MOF-derived NiS / ZnIn2S4 composite material, characterized in that: The MOF-derived NiS / ZnIn2S4 composite material is a rope-grape-like material with a coupled heterogeneous interface formed by the composite of spiral ZnIn2S4 and NiS, wherein the NiS is prepared by using Ni-MOF as a precursor, sulfiding and calcining; and the spiral ZnIn2S4 is obtained by hydrothermal synthesis using polyvinyl pyrrolidone as a directing agent and serine as a template.
2. A MOF-derived NiS / ZnIn2S4 composite material according to claim 1, characterized in that: The preparation method of NiS comprises: S1-1, preparation of Ni-MOF: stirring and dissolving nickel nitrate into an aqueous solution containing methanol, adding sodium citrate and disodium ethylenediaminetetraacetate in sequence to form a mixed solution after dissolution, reacting the mixed solution at 160-210°C for 20-28h, cooling to room temperature, centrifuging and washing with deionized water and ethanol solution, and then drying at 50-70°C for 10-14h to obtain a Ni-MOF precursor; The nickel nitrate, methanol aqueous solution, sodium citrate, and disodium ethylenediaminetetraacetate are added in a ratio of 1-3 g: 30 ml: 1-2 g: 1-3 g; the methanol aqueous solution is obtained by mixing methanol and deionized water in a volume ratio of 1:3; S1-2, preparation of NiS hollow spheres: ultrasonically dissolve the Ni-MOF precursor obtained in S1-1 into ethanol, add thioacetamide; after stirring and dissolving, react at 160-210° C. for 4-10 hours; then cool to room temperature, centrifuge and wash with ethanol, and then dry at 50-70° C. for 10-14 hours to obtain NiS particles, and calcine the NiS particles in a nitrogen atmosphere to obtain NiS. The addition ratio of the Ni-MOF precursor, ethanol and thioacetamide is: 20-40 mg: 40 ml: 100 mg.
3. The MOF-derived NiS / ZnIn2S4 composite material according to claim 2, characterized in that When the NiS particles are calcined in a nitrogen atmosphere, the calcination temperature is 250-350° C. and the calcination time is 20-40 minutes.
4. A MOF-derived NiS / ZnIn2S4 composite material as claimed in claim 3, characterized in that: The method for calcining NiS particles in a nitrogen atmosphere is as follows: firstly, the NiS particles are heated from 20 to 25°C to 250 to 350°C at a heating rate of 3 to 8°C / min, then kept at 250 to 350°C for 20 to 40 minutes, and then cooled to 20 to 25°C at a cooling rate of 5 to 10°C / min.
5. A MOF-derived NiS / ZnIn2S4 composite material according to claim 1, characterized in that: The preparation method of the spiral ZnIn2S4 comprises: 1) Dissolve 0.4-0.7 mmol of zinc nitrate and 0.9-1.2 mmol of indium nitrate in 15-30 mL of deionized water to form a first mixed solution; 2) Add 0.05-0.3 g of polyvinyl pyrrolidone and 0.02-0.07 g of serine to the first mixed solution, stir until dissolved, add 0.02-0.07 mmol / mL of CH3CSNH2 aqueous solution and stir; then stand at 150-200°C for 20-25 hours, and obtain spiral ZnIn2S4 after centrifugal separation, washing and drying.
6. The method for preparing a MOF-derived NiS / ZnIn2S4 composite material according to claim 1, characterized in that: include: Take deionized water, HCl aqueous solution and glycerol and mix them evenly, add NiS and dissolve it by ultrasonication; then add spiral ZnIn2S4, stir and dissolve it, place it in a container, heat it in an oil bath at 70-90℃ for 4-8h, and then cool it; After cooling to room temperature, centrifugation and washing with ethanol solution were performed, and then drying was performed at 50-70°C for 10-14h to obtain NiS / ZnIn2S4; The addition ratio of the deionized water, HCl aqueous solution, propylene glycol, NiS, and spiral ZnIn2S4 is: 30-40 mL: 3-8 mL: 2 mL: 3-20 mg: 140-160 mg, wherein the pH of the HCl aqueous solution is 2.
5.
7. A method for preparing a MOF-derived NiS / ZnIn2S4 composite material as claimed in claim 6, characterized in that: The power of the ultrasound is 300-500W, and the time is 20-35min. In the centrifugal washing, the centrifugal speed is 5000-8000r / min, and the centrifugal time is 4-10min.
8. The use of a MOF-derived NiS / ZnIn2S4 composite material as claimed in claim 1, characterized in that: It is applied in the process of photocatalytic hydrogen evolution.
Citation Information
Patent Citations
NiS<2> / ZnIn<2>S<4> composite material, and preparation method and application thereof
CN110993971A
Heterostructure catalyst for decomposing water into hydrogen by using solar energy and preparation method of catalyst
CN112774696A
Cu-MOF / ZnIn2S4 heterojunction, preparation method and application thereof
CN117160488A